Human endogenous retroviruses in schizophrenia: clinical evidence, molecular mechanisms, and implications - Zhang, Mengyu; Wang, Xiaoge; Liu, Yun; Bao, Chenxuan; Gao, Qing; Mao, Lingxiang (Frontiers in Cellular and Infection Microbiology, 2025)
Human endogenous retroviruses (HERVs), comprising 8% of the human genome, are implicated in schizophrenia, a complex psychiatric disorder driven by genetic, epigenetic, and environmental factors. This review examines the role of HERVs in schizophrenia pathogenesis. We synthesized clinical evidence, molecular mechanisms, and gene-environment interactions from studies on HERVs expression in schizophrenia, focusing on HERV-W and HERV-K in peripheral blood, cerebrospinal fluid, and brain tissues. Elevated HERV-W and HERV-K env and gag transcripts are consistently observed in individuals with schizophrenia, indicating potential diagnostic biomarkers. HERVs contribute to neuroinflammation, neurotoxicity, and epigenetic dysregulation of risk genes. The HERV-W env activates the Toll-like receptor 4 (TLR4)/MyD88 pathway, disrupting glutamatergic and dopaminergic signaling, leading to synaptic dysfunction and neuronal apoptosis. Environmental triggers, such as viral infections and early-life stress, activate HERVs, linking genetic and environmental risks. Variability in HERV expression across disease stages highlights the need for standardized assays and longitudinal studies. Emerging technologies and preclinical models targeting HERV-W env offer promise for developing novel diagnostics and therapies. HERVs serve as pivotal mediators of schizophrenia’s etiology, advancing precision psychiatry through biomarker and therapeutic innovation.